2021
DOI: 10.3390/ijerph182010561
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Impact of the Relative Age Effect on Competition Performance in Swimming: A Systematic Review

Abstract: This systematic review aimed to examine the prevalence of the relative age effect (RAE) in swimming and its impact on competition performance according to different types of interacting constraints. A systematic literature search, following the PRISMA guidelines for preparing systematic reviews, was performed through four electronic databases, and nine studies met the inclusion criteria. The quality of the selected studies was evaluated using STROBE, and an average score of 16.2 points was obtained. In these s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 66 publications
0
21
0
2
Order By: Relevance
“…On the other side, the lowest RAE was found among females in the Junior (U19) group. Lorenzo-Calvo et al (2021) had written a systematic review among swimmers in 6 capital papers. In this particular study, the prevalence of RAE in swimming was observed in 58.65% of participants analyzed, and the effect of RAE was more frequently found among youth categories (decreased as age increased and was inverted among older ones) and among male competitors (two times more than among female swimmers).…”
Section: Legend: N-sample Of Participants Q1-q4-first To the Fourth Q...mentioning
confidence: 99%
See 2 more Smart Citations
“…On the other side, the lowest RAE was found among females in the Junior (U19) group. Lorenzo-Calvo et al (2021) had written a systematic review among swimmers in 6 capital papers. In this particular study, the prevalence of RAE in swimming was observed in 58.65% of participants analyzed, and the effect of RAE was more frequently found among youth categories (decreased as age increased and was inverted among older ones) and among male competitors (two times more than among female swimmers).…”
Section: Legend: N-sample Of Participants Q1-q4-first To the Fourth Q...mentioning
confidence: 99%
“…The existence of the Relative age effect (RAE) is a topic that is often ignored by coaches, but in recent times RAE gained greater attention from sports scientists and the coaching community. In the sports field, relative age can be defined as the chronological age difference that occurs between athletes of the same age group (Lorenzo-Calvo et al, 2021;Diaz del Campo, 2013). The collection of consequences derived from this difference in a birthdate is commonly referred to as the RAE (Lorenzo-Calvo et al, 2021;Barnsley, Thompson, Barnsley, 1985).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though RAE is a widespread phenomenon in different individual 20,21 and invasion team sports [22][23][24][25][26][27] , investigations in water sports focus on swimming [28][29][30] , being scarce in water polo [31][32][33] . In addition to that, the results from studies that investigated RAE in water polo are inconsistent.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, early maturing swimmers are promoted for talent development programs, and potentially highly talented but late maturing swimmers can be deselected and irreversibly lost from the talent program 9 . The dominance of early maturing swimmers and those born early in the year may result in faster race times during adolescence 10 , especially in simultaneous strokes and sprint events 11 . Thus, expectations for talented, but normal or late maturing age-group swimmers would be overestimated.…”
Section: Introductionmentioning
confidence: 99%